Serum gamma-glutamyltransferase and the burden of atherosclerosis in patients with acute coronary syndrome - Mustafa Duran (Türk Kardiyoloji Derneği Arşivi, 2013)
Objectives: We evaluated the relationship between serum gamma-glutamyltransferase (GGT) levels and the burden of atherosclerosis in patients with acute coronary syndrome (ACS). Study design: This study involved 180 patients (139 male, 41 female; mean age 63+-11 years) with the diagnosis of ACS (non- ST elevation myocardial infarction and unstable angina) who underwent coronary angiography on the first day after hospital admission. The burden of atherosclerosis was assessed by the number of involved vessels, and the Gensini and Syntax scores. Serum GGT levels were measured by enzymatic caloric test. Results: Patients with high Syntax scores (≥33) were more frequently diabetic, hypertensive, and had higher GGT and creatinine levels compared to the patients with low Syntax scores (≤23). Similarly, patients with ≥3 diseased vessels were more frequently diabetic, hypertensive, and smokers. In addition, these patients were older and had higher serum glucose, urea and GGT levels. Correlation analysis revealed that the level of GGT was significantly associated with Gensini and Syntax scores, number of diseased vessels, and the number of critical lesions (r=0.378 p<0.001, r=0.301 p<0.001, r=0.159 p=0.036, r=0.355 p<0.001, respectively). Multivariate linear regression analysis demonstrated that increased GGT level was an independent risk factor for high Gensini and Syntax scores (p=0.029 and p=0.035, respectively), together with age (p=0.001 and p=0.002, respectively) and serum glucose levels (p=0.017 and p=0.012, respectively). Conclusion: Serum GGT levels on admission are associated with increased burden of atherosclerosis in patients with ACS. This may account for the cardiovascular outcomes associated with increased GGT levels.